Ligas Sn-Ni: efeitos da taxa de resfriamento e da microestrutura nas propriedades mecânicas de tração - Xavier, Marcella Gautê Cavalcante (2018)
The present investigation examined the microstructural arrangements formed during the transient solidification of the eutectic Sn-0.2wt.%Ni and the hypereutectic Sn-0.5wt.%Ni alloys using two different substrates as mold sheets separating the alloy casting from the cooling fluid: copper and low carbon steel. The examination of the obtained microstructures was carried out highlighting not only the micromorphology aspects of the formed β-Sn phase but also the nature and the shape of the intermetallic compounds (IMCs) developed. The purpose of this research work is to verify the influences that both substrates of different materials and Ni content may have on the alloy solidification kinetics, resultant microstructures and tensile properties of the Sn-Ni solder alloys. The dissolution of Cu from the popper mold in the eutectic alloy contributed to the prevalent growth of the (Cu,Ni)6Sn5 fiber-like eutectic phase along the length of the casting. Furthermore, a β-Sn morphological cellular/dendritic transition occurs in the eutectic alloy against copper mold for ṪE>5.5°C/s. On the other hand, for the alloy solidified against the steel mold, a predominance of the non-equilibrium NiSn4 eutectic phase with plate-like shape has been identified by SEM/EDS. For the solidified hypereutectic Sn-0.5wt.%Ni alloy in copper mold, the results indicate that the increase in Ni content may have influenced both thermal behavior and cellular spacing (λC). A transition from high cooling rate cells to plate like cells characterizes the hypereutectic alloy for ṪE>2.7°C/s. The NiSn4 intermetallic particles are also present in the eutectic mixture of the Sn-0.5wt.%Ni. Experimental growth laws relating the microstructural spacings, λ1,C, to the cooling rate and eutectic growth rate have been proposed, as well as Hall-Petch type experimental equations associated with tensile properties as a function of the length scale of the β-Sn matrix, for both the eutectic and hypereutectic chemistries.